Beyond Infrastructure: How Supervision and Collaboration Shape Effective Islamic Religious Education in Resource-Limited Schools - Alfi Khoirun Nisa; Eka Setya Budi (Managere: Indonesian Journal of Educational Management, 2025)
This study investigates how learning facilities and infrastructure are managed and utilized to support Islamic Religious Education in an elementary school context. The research aims to provide an in-depth understanding of how prayer rooms, teaching aids, and digital media shape students’ learning experiences, particularly in situations where facility limitations remain a structural challenge. Using a qualitative descriptive design, data were collected through semi-structured interviews, field observations, and document analysis involving principals, teachers, students, and school committee members. The findings reveal that systematic supervision plays a crucial role in guiding teachers to make the most of available resources. In contrast, teachers' creativity contributes to the development of additional teaching aids that enhance instructional quality. The study also highlights the importance of collaborative engagement among school residents to support the maintenance and sustainability of learning facilities. These interactions create a supportive environment where even limited facilities can function effectively for religious learning. The implications suggest that schools need adaptive strategies to ensure that learning facilities are sustainably integrated into instructional processes, particularly within resource-constrained settings.